Préface. L’art de vivre, de survivre, de revivre. À l’occasion du 50e anniversaire des études romanes à l’Université de Łódź - Kacprzak, Alicja (The Art of Living, Surviving, Reviving. Studies in Linguistics. The 50th Anniversary of Romance Studies at the University of Łódź, 2022)
This Preface presents the volume The Art of Living, of Surviving, of Reviving. On the occasion of the 50th anniversary of Romance studies at the University of Łódź which was designed to commemorate the 50th anniversary of the reactivation of Romance studies at the University of Łódź, carried out today within the Institute of Roman Studies. At the same time, the book celebrates the 10th anniversary of the creation, within the Institute of Romanesque Studies, of the Department of Italian Philology. These anniversaries take place at the time of the Covid-19 pandemic, an unprecedented event in the global world of the 21st century, with confinement as a compulsory mode of operation for long weeks, even months. The rupture thus brought about undoubtedly led to a new perception of life and of what ił means to live. For more than one, this thick line that separates our existence before and after Covid-19 constitutes a memento inciting to wonder how to live the pandemic and during the pandemic, how to survive it and if it is possible to (re)live completely when it has corne to an end. These questions launched as the driving theme of the commemorative volume have called for a rich and varied reflection contained in 25 articles, falling within different sub-fields of linguistics.